Management of Telogen Effluvium: A Survey among Dermatologists and Dermatology Residents of Nepal - Sharma, Ashu; Khadka, Anupa; Dolma Gurung, Tsering; Shrestha, Dwarika Prasad (Nepal Journal of Dermatology, Venereology & Leprology, 2025)
Introduction: Telogen effluvium (TE) is a common form of non-cicatricial alopecia, marked by excessive shedding of hairs in the telogen phase. Despite its prevalence, there is no consensus on the best approach to diagnosing, investigating, and managing TE, leading to varying practices among dermatologists. This study aims to understand current practices in Nepal regarding the diagnosis and treatment of TE. Objectives: To explore the management modalities of TE among the dermatologists and dermatology residents of Nepal Materials and Methods: An online, questionnaire-based survey was conducted among Nepalese dermatologists and dermatology residents. The questionnaire consisted of twelve multiple-choice questions related to TE. The responses were recorded and analyzed. Results: A total of 150 responses were recorded, with 53.33% attending 5-10 hair loss patients weekly. Most (94%) diagnosed TE based on history and clinical examination, and 82% commonly ordered thyroid function tests. Iron and vitamin deficiency was identified as the leading cause by 78%, and 53.33% felt no treatment was necessary. Counseling (92.66%) and iron/vitamin supplements (88%) were the most frequent management strategies. TE was reported to have a "moderate" impact on Quality of Life (QoL) by 69.33%, and 50.67% of participants reported a “good level” of satisfaction among patients with the outcomes of their treatments. Conclusions: Telogen Effluvium is one of the most common causes of hair fall, with a moderate impact on the quality of life. Most dermatologists agree on many aspects of TE management. A consensus management guideline of TE would be handy.